PERAWATAN KUKU PADA SAPI DI BALAI INSEMINASI BUATAN UNGARAN - , RIA PUTRI PRAPTININGTYAS, drh. Setyo Budhi, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Opus writes this constitute field work practice result at Balai Inseminasi Buatan (BIB) Ungaran, about Hoofcare in Cattle. The purpose of final task with article Hoofcare in Cattle at Balai Inseminasi Buatan Ungaran to know about hoofcare has done in BIB Ungaran and to know about Footrot disease ranging from the causes, transmission, clinical symptoms, treatment, and prevention of disease. Data obtained derived from observation of activities and interviews with officers BIB Ungaran. The result is hoofcare in BIB Ungaran performed three to six months. Cutting hoofs more often done to the cattles inside the cage. The cattles were exposed to the Footrot disease in Balai Inseminasi Buatan Ungaran in the period of 2013 to 2014 are three of the existing 22 bulls. Handling is done by dipping (PK 1 teaspoon, Antisep 300 ml and water to taste). Factors affecting of Footrot disease drainage and exercise. Conclusion, hoofcare and treatment of footrot disease in Balai Inseminasi Buatan Ungaran already good.